Using the amide proton signals of intracellular proteins and peptides to detect pH effects in MRI - Zhou, Jinyuan; Payen, Jean-Francois; Wilson, David A; Traystman, Richard J; van Zijl, Peter C M (Nature medicine, 2003)
In the past decade, it has become possible to use the nuclear (proton, 1 H) signal of the hydrogen atoms in water for noninvasive assessment of functional and physiological parameters with magnetic resonance imaging (MRI). Here we show that it is possible to produce pH-sensitive MRI contrast by exploiting the exchange between the hydrogen atoms of water and the amide hydrogen atoms of endogenous mobile cellular proteins and peptides. Although amide proton concentrations are in the millimolar range, we achieved a detection sensitivity of several percent on the water signal (molar concentration). The pH dependence of the signal was calibrated in situ , using phosphorus spectroscopy to determine pH, and proton exchange spectroscopy to measure the amide proton transfer rate. To show the potential of amide proton transfer (APT) contrast for detecting acute stroke, pH effects were noninvasively imaged in ischemic rat brain. This observation opens the possibility of using intrinsic pH contrast, as well as protein- and/or peptide-content contrast, as diagnostic tools in clinical imaging.